Important criteria for measuring heritage building condition - Zuraidi, Siti Nor Fatimah; Abdul Rahman, Mohammad Ashraf; Akasah, Zainal Abidin (Zes Rokman Resources, 2017)
The excellence condition of a heritage building lies not only in the appearance of its individual elements, but also in the integrity of all its components, considered as unique criteria of the specific construction technology of its time and place. However, these criteria are varied and not specific. Therefore, this study aimed to identify and rank the important criteria for measuring the condition of heritage buildings in Malaysia. Data obtained through questionnaire and analyzed using Average Index (AI) in order to establish the important criteria. Samples were selected from a panel of experts in the field of heritage buildings management including industry players and academicians. The established criteria will be used as components to develop a new method of heritage building condition determination model in Malaysia.